Examining sex differences in DSM-IV narcissistic personality disorder symptom expression using Item Response Theory (IRT) - Hoertel, Nicolas (Psychiatry Res, 2017)
The limited published literature on the subject suggests that there may be differences in how females and males experience narcissistic personality disorder (NPD) symptoms. The aim of this study was to use methods based on item response theory to examine whether, when equating for levels of NPD symptom severity, there are sex differences in the likelihood of reporting DSM-IV-TR NPD symptoms. We conducted these analyses using a large, nationally representative sample from the USA (n=34,653), the second wave of the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC). There were statistically and clinically significant sex differences for 2 out of the 9 DSM-IV-TR NPD symptoms. We found that males were more likely to endorse the item ‘lack of empathy’ at lower levels of narcissistic personality disorder severity than females. The item ‘being envious’ was a better indicator of NPD severity in males than in females. There were no clinically significant sex differences on the remaining NPD symptoms. Overall, our findings indicate substantial sex differences in narcissistic personality disorder symptom expression. Although our results may reflect sex-bias in diagnostic criteria, they are consistent with recent views suggesting that narcissistic personality disorder may be underpinned by shared and sex-specific mechanisms.